The health decision-making process subsidized by cost information - Pereira, Ana Cristina; Ferrari Nunes, Angela Sofia (O Mundo da Saúde, 2011)
Companies daily face decision-making problems that directly threaten their business continuity. A decision analysis comprises using different summary and modeling concepts and techniques towards a better quality in the decision-making process. This research aimed at analyzing the relevance of the cost information in the entrepreneurial decision-making process. A research was carried out in a Diagnostic Cardiology Clinic. It referred to a descriptive research as to the purposes, and field, document and bibliographical researches were conducted as to the means of investigation. The studied Clinic faced an important decision about the hospital’s proposal to increase the transfer of the revenues arising from the provision of services from 20% to 35% and charge a usage fee of the physical space. To decide whether to accept or not the new hospital’s proposal, a thorough analysis of the operating flows and the respective costs involved was made. In the case of the labor of physicians, the remuneration was paid by means of a fixed amount for a 6-hour shift plus the sum per medical examination, when the fixed amount exceeded. It was observed that this form of remuneration burdened the costs of the medical examinations made. Moreover, for the group of physicians, a 79,73% idleness rate was verified owing to the compulsoriness of keeping a medical staff on duty to answer all the hospital’s calls. The Clinic was in a situation of loss. If it accepted the new hospital’s proposal, this situation would become worse by increasing the losses and requiring about 3,265 medical examinations to be made, corresponding to a 147,35% rise in medical services, to achieve the break-even point. The cost information was relevant by contributing to foresee a situation that would be worse if the hospital’s proposal was accepted, thus complying with the first phase of the decision-making process and collaborating on the start of the following phase, that is, creating options for a better negotiation between the parties.